A National Survey of the Perceived Value of American Association of Family and Consumer Science Accreditation. (June 2016) - Pucciarelli, Deanna L.; Hall, Scott; Harden, Amy
Abstract : The purpose of this study was to measure the perceived value of the American Association of Family and Consumer Science (AAFCS) accreditation. The overarching research question was how faculty and administrators at institutions in the United States perceived the value of AAFCS accreditation. The study used an exploratory research method to determine whether there were barriers to institutions obtaining or retaining AAFCS accreditation. A survey was developed and e‐mailed to faculty and administrators in higher education in accredited and unaccredited academic units. Of the 1, 910 e‐mail invitations, 345 returned survey responses, leaving 317 useable surveys. Questions focused on the purposes and benefits as stated by the AAFCS accreditation program. Also, the survey included questions on whether the resources required to obtain certification were worth the benefits from being certified. Results showed that the perceived benefit of accreditation did not differ by participants who were employed in accredited programs, but results differed by AAFCS membership status. Implications suggest support is needed from AAFCS and that there are concerns in regard to competing associations' accreditations.